Equipamiento de Culto Misión Carismática Internacional (2022)
This document develops the thesis work entitled “Equipping the Misión Carismática Internacional worship center, which is based on the design of a complex for the Misión Carismática Internacional church and its immediate context, providing the western florida neighborhood with new public spaces for the residents of the area and the UPZ (zoning planning unit) in general, as well as improving the road and pedestrian infrastructure of the area. The International Charismatic Mission is one of the largest churches in Latin America and the world, and the design of its main headquarters seeks to make up for the capacity of the site, which is decreasing every year due to the increasing number of faithful who congregate there. The multiple trips made by the faithful and members of the ICM are the reason why there is a certain degree of vitality in the area despite the state of the neighborhood.